Maternal Deaths due to Obstetric Haemorrhage in Dodoma Regional Referral Hospital, Tanzania - Mzee M. Nassoro; Enid Chiwanga; Athanase Lilungulu; Deogratius Bintabara (Obstetrics and Gynecology International)
Background. Despite the availability of comprehensive emergency obstetric care at Dodoma Regional Referral Hospital, deaths due to obstetric haemorrhage are still high. This study was carried out to analyse the circumstances that had caused these deaths. Methods. A retrospective review of all files of women who had died of obstetric haemorrhage from January 2018 to December 2019 was made. Results. A total of 18,296 women gave birth at DRRH; out of these, 61 died of pregnancy-related complications of the deceased while 23 (38%) died of haemorrhage, with many of them 10 (44%) between the age of 30 and 34. Many were grand multiparous women 8 (35%) and almost half of them (11 (48%)) had stayed at DRRH for less than 24 hours. More than half (12 (52%)) had delivered by caesarean section followed by laparotomy due to ruptured uterus (8 (35%)). The leading contributing factors to the deaths of these women were late referral (6 (26%)), delays in managing postpartum haemorrhage due to uterine atony (4 (17%)), inadequate preparations in patients with the possibility of developing PPH (4 (17%)), and delay in performing caesarean section (3 (13%)). Conclusion. Maternal mortality due to obstetric haemorrhage is high at Dodoma Regional Referral Hospital where more than one-third of women died between 2018 and 2019. Almost all of these deaths were avoidable. The leading contributing factors were late referral from other health facilities, inadequate skills in managing PPH due to uterine atony, delays in performing caesarean section at DRRH, and inadequate preparation for managing PPH in patients with abruptio placentae and IUFD which are risk factors for the condition. There is a need of conducting supportive supervision, mentorship, and other modes of teaching programmes on the management of obstetric haemorrhage to health care workers of referring facilities as well as those at DRRH. Monitoring of labour by using partograph and identifying pregnant women at risk should also be emphasized in order to avoid uterine rupture.